A morphological sex difference in the neutrophils of the buffalo (Bubalus Bubalis) - Bongso, Tuan Ariffeen; Jayasekera, A. (Malaysian Society of Applied Biology, 1980)
Sexual dimorphism in the nuclei of polymorphonuclear neutrophil leukocytes in swamp buffaloes of Malaysia and Sri Lanka is described. A solitary round nuclear appendage, 1.4μ in diameter with a drumstick form was found only in female buffaloes from both countries, The incidence of the drumstick appendage averaged 3.8 and 4.1% in ten Malaysia and ten Sri Lankan female swamp buffaloes, respectively. The typical drumstick structures had to be distinguished from certain other appendages found in both sexes and a minimum of 500 leukocytes/animal had to Lcexamined to arrive at a sex difference.